Ratio changes between "dose-effect" of working capacity by stimulation influences means for qualified athletes in rowing - Vinogradov V.Ye (Kharkov National Pedagogical University, 2012)
New possibilities of special athlete´s endurance increase in rowing are represented in the article. It founded on athlete´s organism stimulation in 22-24 hours before load in hard load training microcicle. Use of subsidiary means are increase the load influence and raise working capacity in 1-3 large load training after. It is shown by growth of training impulse, index of "dose-effect" influences and by ergomethric force rise in replay of standard physical load. Complex of stimulation influences means application increase the training effect and cumulative effects in it series during hard load training microcicle.